Roles of the Src tyrosine kinases Lck and Fyn in regulating gammadeltaTCR signal strength. - Renee M Laird; Sandra M Hayes (PLoS ONE, 2010)
Lck and Fyn, members of the Src family of tyrosine kinases, are key components of the alphabetaTCR-coupled signaling pathway. While it is generally accepted that both Lck and Fyn positively regulate signal transduction by the alphabetaTCR, recent studies have shown that Lck and Fyn have distinct functions in this signaling pathway, with Lck being a positive regulator and Fyn being a negative regulator of alphabetaTCR signal transduction. To determine whether Lck and Fyn also differentially regulate gammadeltaTCR signal transduction, we analyzed gammadelta T cell development and function in mice with reduced Lck or Fyn expression levels. We found that reducing Lck or Fyn levels altered the strength of the gammadeltaTCR signaling response, with low levels of Lck weakening gammadeltaTCR signal strength and low levels of Fyn augmenting gammadeltaTCR signal strength. These alterations in gammadeltaTCR signal strength had profound effects not only on alphabeta/gammadelta lineage choice, but also on gammadelta thymocyte maturation and gammadelta T cell effector function. These results indicate that the cellular levels of Lck and Fyn play a role in regulating the strength of the gammadeltaTCR signaling response at different stages in the life of the gammadelta T cell.